6 - Political Science and African Political Epistemologies: The Dialectics of Developmentalist vs. Emancipatory Approaches - Nasong’o, Shadrack Wanjala (Africa Development, 2021)
The premise of this article is that there has been a dialectical duality to the political science study of Africa, in terms of scholars and focus. The duality of scholars is represented by African scholars both on the continent and in the diaspora, on one hand, and Africanist scholars (non-African scholars who study Africa), on the other. Much of the political study of Africa has focused on the problematic of development. This political science research focus on the problematic of development gives epistemological priority to generating empirical political knowledge research. In contrast, research emphasis on the problematic of emancipation from oppression and exploitation prioritises an epistemological conception of knowledge that facilitates radical change as it grapples with evaluative moral-ethical issues. The purpose of the article is to examine the dialectical nexus of development- and emancipatory-focused political study of Africa, and the impact and relevance of the corpus of political science epistemologies thus generated. The central argument is that the relevance and implications of political science epistemologies generated via normative and critical approaches have been more profound than those generated via strictly positivist and empirical approaches.